All drinking is not equal: how a social practice theory lens could enhance public health research on alcohol and other health behaviours. (11th July 2017) - Meier, Petra Sylvia; Warde, Alan; Holmes, John
Abstract: Background: The social meanings, settings and habitual nature of health‐related activities and their integration into our daily lives are often overlooked in quantitative public health research. This reflects an overly individualized approach to epidemiological surveillance and evaluations of public health interventions, based on models of behaviour that are rooted in social cognition and rational choice theories. This paper calls for a new approach to alcohol epidemiology and intervention research informed by theories of practice. Argument: Practices are conceptualized as routinized types of human activity that are made up of, and can be recognized by, the coming together of several interwoven elements in the same situation (e.g. materials, meanings, skills, locations, timings). Different practices are interconnected—they can occur simultaneously (e.g. drinking and eating), hold each other in place (e.g. after‐work drinks) or compete for time (e.g. parenting versus socializing). Applying these principles to alcohol research means shifting attention away from individuals and their behaviours and instead making drinking practices an important unit of analysis. Studying how drinking practices emerge, persist and decay over time, how they spread through populations and local or social networks and how they relate to other activities of everyday life promises new insights into how, why, where, when and with whom drinking and getting drunk occur. Conclusions: Theories of practice provide a framework for generating new explanations of stability and change in alcohol consumption and other health behaviours. This framework offers potential for novel insights into the persistence of health inequalities, unanticipated consequences of policies and interventions and new interventions targets through understanding which elements of problematic practices are likely to be most modifiable. We hope this will generate novel insights into the emergence and decay of drinking practices over time and into the geographical and socio‐demographic patterning of drinking. Theories of practice‐informed research would consider how alcohol policies and population‐level interventions might differentially affect different drinking practices.